FINANCIAL RATIOS ANALYSIS WITH THE ALTMAN Z-SCORE TO PREDICT THE LEVEL OF COMPANY'S BANKRUPTCY (PT TIGA RAKSA SATRIA TBK PERIOD 2016-2021) - Hadisty Dewi Septiarini; Abdul Ghofur; Sutinem Sutinem (Jurnal Scientia, 2022)
The purpose of this study was to determine the financial condition of PT Tigaraksa Satria Tbk with financial ratios through the Altman Z-Score method in predicting the potential for bankruptcy of the company. This type of research is descriptive quantitative research. The results of the analysis show that the analysis of financial statements for the period 2016-2021 with financial ratios through the Altman Z-Score method shows that in the period 2016 to 2021 PT Tigaraksa Satria is in a healthy company state.